Delayed ischaemic preconditioning in the presence of galectin‐9 protects against renal ischaemic injury through a regulatory T‐cell dependent mechanism. Issue 10 (October 2016) - Zhang, Bing‐Ying; Fang, Yi; Jiao, Xiao‐Yan; Wu, Sheng; Cai, Jie‐Ru; Zou, Jian‐Zhou; Ding, Xiao‐Qiang
Abstract: Aim: Renal ischaemia/reperfusion injury (IRI) is a complication of major surgeries. Regulatory T cells (Tregs) can suppress immunologic damage in the renal IR. Previous studies indicated that delayed ischaemic preconditioning (IPC) partially attenuates IR by inducing Treg expansion. Galectin‐9 also attenuates inflammation‐related organ injury by expanding Tregs, but it was not used in renal IR yet. Our aim was to test whether IPC combined with galectin‐9 has an increased renoprotective effect. Methods: Mice were divided into five treatment groups ( n =  6 per group): (i) IR group: renal ischaemia/reperfusion group; (ii) IPC‐IR group: IPC followed by renal IR; (iii) IPC‐Gal9‐IR group: Gal‐9 injections during the time between IPC and IR; (iv) IPC‐Gal9‐PC61‐IR group: anti‐CD25 antibody administration apart from IPC, Gal‐9 and IR; (v) sham‐sham group. We assessed the renal function, histopathological scores, and percentages of Tregs and interferon‐γ (IFN‐γ) cells in peripheral bood, spleen, and kidney and compared these values among the different groups. Results: Serum creatinine measured was significantly lower after IPC and even lower in combination with Gal‐9 injection. The histopathological scores for tubulo‐interstitial injury were decreased following IPC and markedly lower after the addition of Gal‐9. The number of kidney infiltrating neutrophils and IFN‐γ secreting CD4+ T cells was diminished in the IPC/Gal9 combination group, while the percentage of Treg cells in the peripheral blood, spleen, and kidney of animals from the IPC‐Gal9‐IR group was also markedly increased. Conclusion: The renoprotective effect of delayed IPC combined with galectin‐9 was superior to IPC alone, through a mechanism related to expansion of regulatory T cells. Summary at a Glance: In this manuscript, Zhang and the coauthors described that the Galectin‐9, a mammalian β‐galactoside binding lectin through a regulatory T‐cell dependent mechanism, has an increased renoprotective effects, which the galectin‐9 may beneficial in renal ischemic injury.